2019
DOI: 10.1136/bmjstel-2018-000387
|View full text |Cite
|
Sign up to set email alerts
|

In situ simulation and its effects on patient outcomes: a systematic review

Abstract: BackgroundThe use of in situ simulation has previously been shown to increase confidence, teamwork and practical skills of trained professionals. However, a direct benefit to patient outcomes has not been sufficiently explored. This review focuses on the effect of in situ simulation training in a hospital setting on morbidity or mortality.MethodsA combined search was conducted in PUBMED, OVID, WEB OF SCIENCE, CINAHL, SCOPUS and EMBASE. 478 studies were screened with nine articles published between 2011 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 31 publications
2
56
0
1
Order By: Relevance
“…BACKGROUND Previous work has demonstrated the utility of in situ simulation to advance health care provider skills and aid in the development of protocols and procedures. 1,2 However, the use of simulation under the constraints inflicted by a pandemic has not yet been addressed. The coronavirus disease 2019 (COVID-19) pandemic posed new challenges to the execution of in situ simulation in the emergency department (ED), as well as timesensitive pressures for the development of protected code blue and intubation protocols.…”
Section: Abstract: Pandemic Simulation Videomentioning
confidence: 99%
“…BACKGROUND Previous work has demonstrated the utility of in situ simulation to advance health care provider skills and aid in the development of protocols and procedures. 1,2 However, the use of simulation under the constraints inflicted by a pandemic has not yet been addressed. The coronavirus disease 2019 (COVID-19) pandemic posed new challenges to the execution of in situ simulation in the emergency department (ED), as well as timesensitive pressures for the development of protected code blue and intubation protocols.…”
Section: Abstract: Pandemic Simulation Videomentioning
confidence: 99%
“…Location is also relevant, as 'in situ simulation'-"taking place in the actual patient care setting/environment" 9 -affords a closer connexion to the physical environment for 'real', often ad hoc teams, to identify enablers or barriers for QI interventions. 10 However, the effect could also lie in simulation shaping the culture and relationships 11 12 that underpin and support structural or process specific interventions.…”
Section: How Why or When Simulation Work For Improving Care Is A Momentioning
confidence: 99%
“…Numerous case study examples of using simulation to improve patient care are now being synthesised in systematic reviews, 10 yielding practical guidelines for using in situ simulation in QI, and building conceptual frameworks for how impacts are achieved. Sollid et al reported on a consensus process "to define priorities in healthcare simulation that contribute the most to improve patient safety", 24 which included two of the five identified priorities clearly at the interface with QI: effectiveness and system probing.…”
Section: Editorialmentioning
confidence: 99%
“…The difficulty of demonstrating changes in an outcome measure is highlighted by the rarity of studies demonstrating improvement in outcomes related to simulation. 4…”
Section: Discussionmentioning
confidence: 99%